Teacher’s Perceptions of the English Teacher Competences of Senior High School in Pangkep - Sri Fausyia; Syarifuddin Dollah; La Sunra (EduLine: Journal of Education and Learning Innovation, 2024)
The objective of this study is to find out teachers' perceptions of English teachers' competence in senior high schools in Pangkep. This study uses a qualitative method. The population of this study is teachers in senior high schools in Pangkep, with the sample consisting of English teachers in SMAN 2 Pangkep, SMAN 9 Pangkep, and SMAN 10 Pangkep. The research instrument used is interviews. The results show that English teachers' perceptions of competence include four aspects: professional competence, personality competence, pedagogical competence, and social competence, all of which are important and interrelated to carry out tasks effectively and professionally.